Cue salience of the use of an electronic nicotine delivery system (ENDS) device marketed to women. (January 2020) - Vena, Ashley; Miloslavich, Krista; Cao, Dingcai; King, Andrea
Abstract: Introduction: Passive exposure to the use of electronic nicotine delivery systems (ENDS or e-cigarettes) has been shown to generalize as a smoking cue. As young adult women in particular are increasingly targeted by ENDS distributors, the present study examined whether passive exposure to the use of a female-marketed ENDS product selectively enhanced smoking urge, cigarette and e-cigarette desire, and smoking behavior among women (vs men) smokers. Methods: Using a mixed design, young adult smokers ( n = 64; mean age 28.2 yrs.; ≥5 cigarettes/day) observed a study confederate drink bottled water (control cue) and then vape a female-marketed tank-based ENDS (active cue). Main measures were the Brief Questionnaire of Smoking Urges (BQSU) and visual analog scales (VAS) for cigarette and e-cigarette desire pre- and post-cue exposure, followed by a smoking latency task. Results: Compared to the control cue, the female-marketed ENDS cue increased smoking urge and desire for cigarettes and e-cigarettes to a similar extent in women and men. It also affected subsequent smoking behavior similarly between the sexes, with 68% of men and 58% of women opting to smoke (vs. obtaining monetary reinforcers). Conclusions: Both women and men were sensitive to the use of the female-marketed ENDS as a smoking cue. Consistent with prior work by our group, findings demonstrate the cue salience of ENDS, which may be attributable to the aspects of vaping that resemble traditional smoking (e.g. hand-to-mouth and inhalation and exhalation behaviors). Highlights: Smoking urge and cigarette and e-cigarette desire ratings were higher after ENDS exposure compared with neutral cue exposure Women and men had similar sensitivity to a female-marketed ENDS cue The cue salience of ENDS may be independent of the device's physical appearance